PALEOHISTORY OF SOUTHWESTERN KYZYLKUM (TAMADDUN NURI JURNALI, 2025)
This article is devoted to the study of the southwestern Kyzylkum, which was mastered by our primitive ancestors starting from the Middle Paleolithic, the use of workshops specializing in the manufacture of stone tools for hunting and gathering, and the unique artifacts that have survived to our time, as well as their lifestyle and economic life using technical and typological methods developed by world paleolithic scholars, are revealed.